Implementation of Scrum Method for Keep Wallet Application Design - Khasanah, Fitrotul; Sarmini, Sarmini (International Journal of Informatics and Information Systems, 2023)
In a volatile economy, the Keep Wallet app was developed as a solution to help individuals and businesses manage financial difficulties. The purpose of this application is to provide users with the ability to plan, manage, and control their financial resources with the intention of maximizing value for shareholders or business owners. This research not only evaluates the use of the Scrum method in the development of the Keep Wallet application, but also analyzes whether the method can create high-quality software that meets user needs, as well as have the ability to adopt changes easily. The results show that the use of the Scrum method in the development of this application has a positive impact, improving the quality and productivity of software development, making it easier to prioritize tasks, and providing better customer satisfaction. This research provides evidence that the Scrum method is effective in overcoming financial difficulties through the development of software applications, and the results can serve as a basis for the development of other applications that face similar problems, as well as increase understanding of the benefits of using the Scrum method in software development.